Caracterización físico – mecánica y química de arcillas del sector Sur – Oeste de la Cuenca Sedimentaria Miocénica de Loja - Valle Bustamante, Ángel Leonardo (2015)
In this research we had perform a physica - mechanical and chemical characterization of the clay from the South west sedimentary miocene basin of Loja. There was performed a geologic description of the zone were 10 samples were taken, that samples were located in the sedimentary formations of Quillolaco, San Cayetano and Tigral. The samples were processed in the geology and mines laboratory, certain processes were applied at this samples including natural drying, crushing, sieving and the elimination of organic matter and carbonate. After doing this, physical, mechanical and chemical trials were performed and we got materials of high plasticity found in the group of the smectites. With the XRD performed by Proinstra we could determinate their mineralogy that is basically based in the montmorillonite, illite, kaolinite and quartz. The analysis of the final results led the elaboration of a map of 1:15.000 scale of the interest zones were the samples were taken